The thigh and leg of Homo naledi. Issue 104 (March 2017) - Marchi, Damiano; Walker, Christopher S.; Wei, Pianpian; Holliday, Trenton W.; Churchill, Steven E.; Berger, Lee R.; DeSilva, Jeremy M.
Abstract: This paper describes the 108 femoral, patellar, tibial, and fibular elements of a new species of Homo ( Homo naledi ) discovered in the Dinaledi chamber of the Rising Star cave system in South Africa. Homo naledi possesses a mosaic of primitive, derived, and unique traits functionally indicative of a bipedal hominin adapted for long distance walking and possibly running. Traits shared with australopiths include an anteroposteriorly compressed femoral neck, a mediolaterally compressed tibia, and a relatively circular fibular neck. Traits shared with Homo include a well-marked linea aspera, anteroposteriorly thick patellae, relatively long tibiae, and gracile fibulae with laterally oriented lateral malleoli. Unique features include the presence of two pillars on the superior aspect of the femoral neck and a tubercular distal insertion of the pes anserinus on the tibia. The mosaic morphology of the H. naledi thigh and leg appears most consistent with a species intermediate between Australopithecus spp. and Homo erectus and, accordingly, may offer insight into the nature of the earliest members of genus Homo . These fossils also expand the morphological diversity of the Homo lower limb, perhaps indicative of locomotor diversity in our genus.